Structure–Function Analysis of SMAX1 Reveals Domains That Mediate Its Karrikin-Induced Proteolysis and Interaction with the Receptor KAI2 - Khosla, Aashima; Morffy, Nicholas; Li, Qingtian; Faure, Lionel; Chang, Sun Hyun; Yao, Jiaren; Zheng, Jiameng; Cai, Mei L.; Stanga, John; Flematti, Gavin R.; Waters, Mark T.; Nelson, David C. (The Plant cell, 2020)
Karrikins (KARs) are butenolides found in smoke that can influence germination and seedling development of many plants. The KAR signaling mechanism is hypothesized to be very similar to that of the plant hormone strigolactone (SL). Both pathways require the F-box protein MORE AXILLARY GROWTH2 (MAX2), and other core signaling components have shared ancestry. Putatively, KAR activates the receptor KARRIKIN INSENSITIVE2 (KAI2), triggering its association with the E3 ubiquitin ligase complex SCF and downstream targets SUPPRESSOR OF MAX2 1 (SMAX1) and SMAX1-LIKE2 (SMXL2). Polyubiquitination and proteolysis of SMAX1 and SMXL2 then enable growth responses to KAR. However, many of the assumptions of this model have not been demonstrated. Therefore, we investigated the posttranslational regulation of SMAX1 from the model plant Arabidopsis ( ). We find evidence that SMAX1 is degraded by KAI2-SCF but is also subject to MAX2-independent turnover. We identify SMAX1 domains that are responsible for its nuclear localization, KAR-induced degradation, association with KAI2, and ability to interact with other SMXL proteins. KAI2 undergoes MAX2-independent degradation after KAR treatment, which we propose results from its association with SMAX1 and SMXL2. Finally, we discover an SMXL domain that mediates receptor-target interaction preferences in KAR and SL signaling, laying the foundation for understanding how these highly similar pathways evolved to fulfill different roles.